Konstruksi Sosial dan Politik dalam Dinamika Perang Dagang AS-Tiongkok - Lutfia Firdaus; Muhammad Daru Wisesha; Muhammad Fajar Maliki; Fathir Bagas Maulana; Indyra Putri Ramadhani (CV. ULIL ALBAB CORP, 2026)
The trade war between the United States and Tiongkok is one of the most significant global economic phenomena today, as it reflects not only economic rivalry but also deeper geopolitical tensions (Zeng, Li, & Tan, 2022; Grosse, Lu, & Shenkar, 202, p. 598). This conflict not only has an impact on the stability of international trade, but also reflects structural tensions in bilateral relations between the two countries. The protectionist policies, economic sanctions and technological restrictions imposed show the role of social construction and economic identity in the direction of national trade policy. This research aims to analyze how the United States and Tiongkok trade war is constructed through political and economic debates, as well as evaluating its impact on international trade standards. The method used is a descriptive explanative approach, with secondary data collection from various sources such as books, journal articles, online publications, and official reports from relevant institutions. The research results show that the trade war between the United States and Tiongkokdoes not only reflect economic competition, but is also used as a political instrument in forming new norms in the global trade order. This conflict has also triggered changes in the dynamics of economic alliances and influenced international trade policy more broadly, with the potential to change the structure of the world economy in the future.